1998
DOI: 10.3733/ca.v052n02p34
|View full text |Cite
|
Sign up to set email alerts
|

Ravenous Formosan subterranean termites persist in California

Abstract: Soldiers are distinguished by the dark head capsule and long mandibles. Workers hatch from eggs laid by the queen and are the only stage that feeds on wood. Colonies can attain 2 million workers within 5 years. The first reported case of a nonnative termite species being introduced and established in California was the Formosan subterranean termite, which was discovered in San Diego County in 1992. Because this termite can exact tremendous damage within a relatively short time, the affected area was defined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…1C; Appendix, Table A1). In 1992, a sizable population of C. formosanus was found in a neighborhood of La Mesa, California (Atkinson et al 1993), which was reported to have persisted through 1997 following termiticidal treatments (Rust et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1C; Appendix, Table A1). In 1992, a sizable population of C. formosanus was found in a neighborhood of La Mesa, California (Atkinson et al 1993), which was reported to have persisted through 1997 following termiticidal treatments (Rust et al 1998).…”
Section: Introductionmentioning
confidence: 99%